EVALUATION OF THE IMPLEMENTATION OF THE GOVERNMENT PURCHASE PRICE GRATITUDE ABSORPTION PROGRAM IN XXX DISTRICT, ACEH PROVINCE - Rusdi Faizin; Dedy Darmansyah; Maulidil Fajri; Ina Yuyun (CV. Radja Publika, 2025)
This study aims to evaluate the effectiveness of the implementation of the Government Purchase Price (HPP) policy in XXX Regency, a rice production center in Aceh Province. The method used in this study is the Importance-Performance Analysis (IPA) approach to assess farmer satisfaction and perceptions of the Government Purchase Price policy. The results show that most indicators have a high level of importance and performance, such as the availability of fertilizers and pesticides, land productivity, facilities and infrastructure, the availability of extension workers, and government program support. These factors are the main strengths that need to be maintained to maintain the sustainability of farming businesses. However, several important aspects were also found to have low performance, such as the price of grain according to the Government Purchase Price, transparency and speed of absorption by Bulog, access to financing, and suboptimal farmer institutions. This indicates the need for more attention to the agricultural marketing system and empowerment of farmer institutions to improve the welfare and competitiveness of farmers in XXX Regency.